ӨТЕШ ДӨРЕТИЎШИЛИГИНДЕ ШАЙЫРЛАР ОБРАЗЫНЫҢ ЖАСАЛЫЎЫ - Давлетов, Б.А. (FAN va JAMIYAT, 2025)
The article analyzes the artistic works of the representative of the Karakalpak lyricism of the 19th century, Utesh. The features of creating an artistic image in the poet's works are studied using the example of the texts of the work. The description of the images of the poets Jiyen, Kunhozha, Ajinyoz, Berdak in his songs is revealed.